2020
DOI: 10.1055/s-0040-1712147
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Issues in Pediatric Regulatory Studies Involving Placebo Treatment

Abstract: Separate pediatric studies for antiepileptic drugs (AEDs) emerged with general separate drug approval in children and were defined by the U.S. Food and Drug Administration (FDA) as <17 years and by the European Union (EU) as <18 years. These administrative age limits are necessary in pediatrics, but they correspond variably with the physiological maturity of young patients and are not helpful for therapeutic decisions or as study inclusion criteria. AEDs are often effective for partial onset seizures (PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Antiepileptic drugs work in both adults and children. 65 Other clinical areas still use "pediatric," e.g. the International Pediatric Multiple Sclerosis Study Group (IPMSSG).…”
Section: Discussionmentioning
confidence: 99%
“…Antiepileptic drugs work in both adults and children. 65 Other clinical areas still use "pediatric," e.g. the International Pediatric Multiple Sclerosis Study Group (IPMSSG).…”
Section: Discussionmentioning
confidence: 99%
“…We propose to put pediatric drug development into the framework of past questionable studies that were reported in 1966 by Beecher, 21 and the Tuskegee study, terminated in 1972. 22,23 The moral imperative of pediatric drug development that demands separate studies in children appears to be noble, 16 but only as long as we do not challenge what the terms child and pediatric mean. [8][9][10]15,[18][19][20] Pediatric drug development has also created numerous conflicts of interest.…”
mentioning
confidence: 99%